2020
DOI: 10.1007/s13399-020-00739-5
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of magnetic porous carbon monolith from waste corrugated cardboard box for solar steam generation and adsorption

Abstract: Porous carbon monoliths (PCMs) were prepared from waste corrugated cardboard box (WCCB) via slurrying in FeCl 3 solution followed by molding and thermal treatment. The thermal process was analyzed by a thermogravimetric analyzer coupled with a Fourier transform infrared spectrometer. The evolution of physicochemical characteristics of PCMs was studied. The photothermal conversion and solar steam generation performances of the optimal sample (PCM Fe/600 ) were evaluated. The adsorption properties of PCM Fe/600 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…The evaluation was completed by placing the samples on top of a heating plate with a temperature set at 100 °C for 1 H. As anticipated, MCFPs manifest superb heat insulating ability compared to the commercially available sound absorbing material as reflected in Figure 6f. This is due to the presence of CBFs which was proven to be a good choice for thermal insulation 19,42 by several researchers. Its thermal insulating property was even intensified when the compressed fibers of the corrugated cardboard box were milled, which increases the surface area.…”
Section: Wettabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation was completed by placing the samples on top of a heating plate with a temperature set at 100 °C for 1 H. As anticipated, MCFPs manifest superb heat insulating ability compared to the commercially available sound absorbing material as reflected in Figure 6f. This is due to the presence of CBFs which was proven to be a good choice for thermal insulation 19,42 by several researchers. Its thermal insulating property was even intensified when the compressed fibers of the corrugated cardboard box were milled, which increases the surface area.…”
Section: Wettabilitymentioning
confidence: 99%
“…Carton boxes or commonly known as corrugated cardboard boxes are bountiful due to their vital use in packaging and delivery service industries, which is why it has been frequently recycled and exhausted. Textile, 18 solar steam generation and adsorption, 19 thermal insulation, 20 and acoustic absorber 21 are some of the applications of recycled/upcycled waste cardboard boxes. It has various functions due to its high recyclability, biodegradability, ecological material, and high structural strength.…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] In particular, the hard carbon derived from various biomass precursors, including peat moss, banana peels, corn cob, silk, wood cellulose, leaf and peanut shell, has gained significant attention and is currently under extensive research. [32][33][34][35][36][37][38][39][40][41] However, the high cost of hard carbon materials, resulting in initial Coulombic efficiencies below 75 % and capacities below 300 mA • g À 1 due to the formation of the solid electrolyte interface (SEI) layer, remains a major obstacle to their industrialization. [38] This study reports the preparation of hard carbon materials from bamboo powder waste via a high-temperature pyrolysis route and its use as anodes for SIBs.The electrochemical performance of the hard carbon derived from bamboo powder was found to be dependent on the carbonization temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that hard carbon materials are the most promising candidates for anode materials in sodium‐ion battery applications due to their larger interlayer distance, high capacity, excellent cycling stability, and lower operating potential [29–31] . In particular, the hard carbon derived from various biomass precursors, including peat moss, banana peels, corn cob, silk, wood cellulose, leaf and peanut shell, has gained significant attention and is currently under extensive research [32–41] . However, the high cost of hard carbon materials, resulting in initial Coulombic efficiencies below 75 % and capacities below 300 mA ⋅ g −1 due to the formation of the solid electrolyte interface (SEI) layer, remains a major obstacle to their industrialization [38] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation